Association between female circulating heavy metal concentration and abortion: a systematic review and meta-analysis - Ren, Meiqi; Wang, Liantong; Wen, Liqin; Chen, Jinghua; Quan, Song; Shi, Xiao (Frontiers in Endocrinology, 2023)
Objective: This study aims to evaluate the association between blood heavy metal (zinc (Zn), copper (Cu), lead (Pb) and cadmium (Cd)) concentration and spontaneous abortion (SA) and recurrent pregnancy loss (RPL), and explore the possible endocrine dysfunction involving in it.2 Method: Literature search was performed in PubMed, Embase, Cochrane Library, and Web of Science databases up to April 2023. The overall effects were expressed as standard mean difference (SMD). Subgroup analysis was performed according to the type of abortion (SA and RPL). Stata 16.0 was utilized for data analysis. Results: Based on the integrated findings, abortion women showed significantly lower Zn (SMD = -1.05, 95% CI: -1.74 --0.36, p = 0.003) and Cu concentration (SMD = -1.42, 95% CI: -1.97 --0.87, p < 0.001) and higher Pb (SMD = 1.47, 95% CI: 0.89 -2.05, p < 0.001) and Cd concentration (SMD = 1.15, 95% CI: 0.45 -1.85, p = 0.001) compared with the normal pregnant women. Subgroup analysis showed that Zn and Cu deficiency and Cd and Pb exposure were significantly (p < 0.05) associated with RPL; while Cu deficiency and Cd and Pb exposure were significantly (p < 0.05) associated with SA. Conclusion: The Zn and Cu deficiency and Pb and Cd exposure were associated with abortion. Endocrine dysfunction, such as insulin resistance, vitamin D insufficiency, and abnormal thyroid and sex hormone concentrations, is supposed to have involved in heavy metals related abortion.